Proceedings of the 6th International Conference on Educational Technologies 2019 2019
DOI: 10.33965/icedutech2019_201902c008
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Support for the Development of Novice Teachers’ Professional Identities

Abstract: Teaching profession requires teachers to be prepared with skills and knowledge to overcome challenges related to subject matter, students, colleagues and personal matters. In order to become an outstanding teacher, one has to undergo formal as well as informal professional development experiences. This study aims to explore the challenges faced by novice teachers and the sources they turned to in order to resolve these challenges. The research participants were three novice teachers who are currently in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…Chua et al (2020) found the benefits of PLC among teachers. This parallels the findings of Fariza and Hazrati (2019) findings that PLC is very suitable and effective in supporting novice teachers in dealing with problems and difficulties in classroom learning through sharing sessions with more experienced and skilled teachers. School leaders should create a learning culture by applying transformational leadership.…”
Section: Transformational Leadership Theorysupporting
confidence: 86%
“…Chua et al (2020) found the benefits of PLC among teachers. This parallels the findings of Fariza and Hazrati (2019) findings that PLC is very suitable and effective in supporting novice teachers in dealing with problems and difficulties in classroom learning through sharing sessions with more experienced and skilled teachers. School leaders should create a learning culture by applying transformational leadership.…”
Section: Transformational Leadership Theorysupporting
confidence: 86%
“…Novice teachers' first years of a job are often a difficult period for them, as many of them feel ineffective, and insecure and are left isolated with no support or guidance from experienced teachers and school heads, which affects their job performance. Concluded by Khalid & Husnin (2019) found that the main supportive elements found to help these teachers in solving their problems are support from senior teachers, colleagues, and family, and information available on the internet.…”
Section: Supportmentioning
confidence: 99%